Coordinated antiinflammatory effects of interleukin 4: interleukin 4 suppresses interleukin 1 production but up-regulates gene expression and synthesis of interleukin 1 receptor antagonist. - Vannier, E (1992)
Interleukin 1 receptor antagonist (IL-1ra), a naturally occurring polypeptide with amino acid sequence homology to interleukin 1 alpha (IL-1 alpha) and interleukin 1 beta (IL-1 beta), prevents Escherichia coli-induced shock and death. Both IL-1 and IL-1ra are produced by monocytes stimulated with lipopolysaccharide (LPS). Because interleukin 4 (IL-4) suppresses IL-1 production, we investigated whether IL-4 modulated IL-1ra synthesis in LPS-stimulated human peripheral blood mononuclear cells. IL-1 beta and IL-1ra were measured by specific RIAs. IL-4 alone (0.01-100 ng/ml) did not stimulate IL-1 beta synthesis but rather induced IL-1ra (4.82 +/- 0.94 ng/ml). LPS induced synthesis of both IL-1 beta (6.67 +/- 1.06 ng/ml) and IL-1ra (10.77 +/- 2.79 ng/ml). IL-4 suppressed LPS-induced IL-1 beta mRNA accumulation and synthesis. However, IL-4 acted synergistically with LPS in inducing IL-1ra. IL-4 enhanced LPS-induced IL-1ra mRNA accumulation 4-fold and IL-1ra protein synthesis nearly 2-fold. Moreover, IL-1ra mRNA levels were maximal after 6 hr of exposure to LPS but peaked within the first 3 hr in the presence of IL-4. IL-4 added as late as 12 hr after LPS stimulation still enhanced IL-1ra synthesis. In human peripheral blood mononuclear cells stimulated with IL-1 alpha, IL-4 markedly suppressed IL-1 beta production but enhanced IL-1ra synthesis greater than 2-fold. Because IL-4 favors synthesis of the natural antagonist IL-1ra over synthesis of the agonist IL-1, IL-4 may exert potent antiinflammatory effects on host responses to Gram-negative infections.